Milk yield characterization (from 1986 to 2007) in Cuban dairy Zebu cattle genotypes (? Zebu: ? Holstein) and their crossbreds - Rodr?guez, Yusleiby; Ponce de Le?n, Rafael (Cuban Journal of Agricultural Science, 2011)
Milk yield (1986-2007) was characterized in Cuban dairy cows of Zebu genotypes (? Zebu: ? Holstein, after inter-se mating), (? Zebu: ? Holstein and dairy Zebu crossbreds, cows with dairy Zebu sires), managed as dual-purpose. The traits under study were total milk yield, lactation length, and milk yield/d (1517 records). Linear models were applied through the GLM procedure of SAS, including, as fixed effects, the genotype, the parturition year, the parturition season, the herd, the number of lactation, and the interaction year x parturition season. Besides, the influence of high and low input availability (before and after 1991) on milk yield was also analyzed. The significance of the genotype, the parturition year, and the herd was obtained in the three traits. The number of lactation was significant for total milk yield and milk yield/d, while the interaction parturition year x bimester was also significant for the lactation length and the milk yield/d. The season was never significant. The highest productions were reported in the crossbred (1266 ? 66kg) and in the ? (1240 ? 61kg) animals, while the poorer were in the Cuban dairy Zebu (1059 ? 36kg). The lack of resources (since 1991) provoked considerable fall in milk productions, not surpassing anew 1000 kg of total milk yield as average. The distribution of parturitions throughout the year was relatively stable for the three genotypes, with slight higher proportion of parturitions from January to April. This corresponded to the highest number of gestations during the periods of highest temperatures, rainfall, and pasture availability. These genotypes are an alternative to milk production with low inputs. Key words: Cuban dairy Zebu, milk yield, calving year.